2010
DOI: 10.1111/j.1460-9592.2010.03397.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral bioavailability of clonidine in children

Abstract: Clonidine administered with an apple fruit drink displays a variable and relatively slow absorption after oral administration (T(max) 1.04 h, C(max) 0.77 mcg·l(-1)). The oral bioavailability was 55.4%, which is less than reported in adults. Consequently, higher oral doses of clonidine (per kg) are required when this formulation is used to achieve concentrations similar to those reported in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 29 publications
4
44
1
Order By: Relevance
“…In our study, peak clonidine serum levels were reached at about 60 min post-dose and concentrations declined only slowly thereafter. This observation matches previously published data, which showed peak plasma concentrations at 60 min post-dose [13]. The large interindividual variation can in part be attributed to interindividual differences in oral bioavailability, which is estimated at 46.9-65.4% [13].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our study, peak clonidine serum levels were reached at about 60 min post-dose and concentrations declined only slowly thereafter. This observation matches previously published data, which showed peak plasma concentrations at 60 min post-dose [13]. The large interindividual variation can in part be attributed to interindividual differences in oral bioavailability, which is estimated at 46.9-65.4% [13].…”
Section: Discussionsupporting
confidence: 79%
“…This observation matches previously published data, which showed peak plasma concentrations at 60 min post-dose [13]. The large interindividual variation can in part be attributed to interindividual differences in oral bioavailability, which is estimated at 46.9-65.4% [13]. It may also be due to the fact that an intravenous formulation was administered orally, which may have different pharmacological properties than tablets intended for oral administration.…”
Section: Discussionsupporting
confidence: 76%
“…At least one population pharmacokinetic study has been published in children and adolescents (0-15 years of age) who received CLON-IR by intravenous, rectal, and epidural administration during anesthesia, which determined that by 1 year of age, 82% of the adult clearance rate is achieved (Potts et al 2007). Of significance is a recent finding of reduced bioavailability in children (3-10 years of age) who received CLON-IR orally (Larsson et al 2011). CLON-IR bioavailability was found to be significantly less (55.4% vs. 75-100% in adults) and more erratic (i.e., higher coefficient of variation) in children when compared with adults (Larsson et al 2011).…”
Section: Pharmacokineticsmentioning
confidence: 95%
“…The fairly rapid decline in plasma level following a single acute dose is seen despite the fairly long half-life of GUAN-IR (i.e., *16 hours) (Shojaei et al 2006;Newcorn et al 2011b). Early pharmacokinetic studies in adults have shown that the bioavailability of oral CLON-IR is high, ranging from 75% to 100%, and that 40-75% is excreted unchanged in the urine (Davies et al 1977;Arndts 1983;Larsson et al 2011). These early studies of CLON-IR are complicated by the use of radioimmunoassay (Arndts 1983;Cunningham et al 1994) which exhibited cross-reactivity with at least one metabolite.…”
Section: Pharmacokineticsmentioning
confidence: 96%
“…The oral bioavailability of clonidine is also poor (F = 0.55) in children 3-10 years. Consequently, larger oral doses (per kg) are required when this formulation is used to achieve concentrations similar to those reported in adults [78].…”
Section: Alternative Delivery Routesmentioning
confidence: 99%